Újrajátszás és körforgás: színház, tánc, történet - Deres, Kornélia (Studia Litteraria, 2024)
In recent decades, contemporary dance and theatre performers have explored various ways in which bodily energies, sounds, movements, gestures, and choreographies can initiate dialogues with the past. Current artistic encounters with past historical events have thus entered the realm of fluidity, eventfulness, and, in some cases, destabilization. The article discusses how ]eatre, Art, and Performance Studies have integrated the notion of repertoire and re-enactment as body-based methods of addressing the past. Calling attention to the connection between archival and performative practices, the article presents two brief case studies on how (re-)enactment can become the basis of various dance and theatre productions. While works by the Természetes Vészek Kollektíva (Hungarian Collective of Natural Disaster) underlined the circularity of historical and aesthetic dynamics, a production by the US-based Wooster Group showed the vital and subversive nature of presence and acting.